Pharmacological treatment of tics in Gilles de la Tourette Syndrome - Andrea E. Cavanna; Andrea Nani (Clinical Management Issues, 2011)
Tourette syndrome is a neurodevelopmental disorder characterised by the chronic presence of multiple motor tics (e.g. eye blinking, shoulder shrugging, etc.) and at least one vocal/phonic tic (e.g. grunting or sniffing). The clinical picture of patients with Tourette syndrome is often complicated by tic-related behavioural problems and associated psychopathology. The pathophysiology of Tourette syndrome is poorly understood, however converging evidence from neuroimaging studies suggests abnormalities within the fronto-striatal pathways. The pharmacological management of the tic symptoms focuses on the dopaminergic and noradrenergic pathways and aims to improve the health-related quality of life of patients.